LAYANAN BIMBINGAN KELOMPOK TEKNIK DISKUSI KELOMPOK DALAM MENINGKATKAN EKSPLORASI KARIR SISWA - Devi Nurul Fikriyani (Universitas Sultan Ageng Tirtayasa, 2023)
Abstrack The purpose of writing this article is to be able to provide direction for students to increase career exploration. In addition to the guidance service using this group discussion technique, students can express opinions and discuss important topics related to careers, develop values, and develop steps. joint steps to resolve problems discussed and discussed in group situations. Because according to researchers there is no way for counselors to support increasing career exploration because counselors have difficulty preparing media related to this. The method used is through literature studies and also from various relevant sources that support this article. The points that will be discussed in this article are career exploration and group guidance services. Group discussion techniques. Keywords: Group Guidance, Discussion Techniques, Career Exploration